2002
DOI: 10.1074/jbc.m202387200
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Eicosapentaenoic Acid in Hippocampus of Rats Exposed to γ-Irradiation

Abstract: Exposure to irradiation leads to detrimental changes in several cell types. In this study we assessed the changes induced in hippocampus by exposure of rats to whole body irradiation; the findings reveal that irradiation leads to apoptotic cell death in hippocampus, and as a consequence, long term potentiation in perforant path-granule cell synapses is markedly impaired. The evidence is consistent with the view that irradiation induced an increase in reactive oxygen species and that this leads to stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 73 publications
4
93
0
1
Order By: Relevance
“…However, few studies reported the involvement of MAPKs in the process. Two studies from the same group revealed that radiation activated JNK in the hippocampus and induced apoptosis, with the main focus on neuronal cell death (Lonergan et al, 2002;Lynch et al, 2003). In line with these studies, we have clearly demonstrated that JNK mediated radiation-induced apoptosis in NSCs.…”
Section: Discussionsupporting
confidence: 85%
“…However, few studies reported the involvement of MAPKs in the process. Two studies from the same group revealed that radiation activated JNK in the hippocampus and induced apoptosis, with the main focus on neuronal cell death (Lonergan et al, 2002;Lynch et al, 2003). In line with these studies, we have clearly demonstrated that JNK mediated radiation-induced apoptosis in NSCs.…”
Section: Discussionsupporting
confidence: 85%
“…Cell biological and molecular studies suggest that omega-3 fatty acids modulate membrane fluidity (Hashimoto et al, 1999), dopaminergic (Piomelli, 1994) and serotonergic (Yao et al, 2004) neurotransmission, and differentially alter gene expression (Kitajka et al, 2002;Salvati et al, 2004). Furthermore, preclinical studies suggest that omega-3 fatty acids have neuroprotective properties Lynch et al, 2007;Martin et al, 2002). Animal and human studies provide ample evidence that essential fatty acid deprivation during pregnancy is associated with developmental and behavioral abnormalities (Innis et al, 1999;Wainwright et al, 1994a, b) that are ameliorated by essential fatty acid supplementation (Helland et al, 2003;Wainwright et al, 1994a, b).…”
Section: Introductionmentioning
confidence: 99%
“…45 Recently, it has been shown that the essential fatty acid precursor eicosapentaenoic acid reduced ROS levels and resulted in less radiation-induced injury in the adult rat brain. 17 Hq mice are more susceptible to oxidative stress, 32,34 but the free radical scavenger edaravone did not provide any beneficial effects, as judged by the SVZ size reduction 7 days after IR. This stands in contrast to a study showing in vivo The SVZ areas in Wt, Het and Hq mice were measured in the contra-and ipsilateral hemispheres 7 days after IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, no effective methods for protecting the normal brain tissue have been established and there is a lack of animal models investigating strategies to limit the debilitating effects of cranial RT. [14][15][16][17][18][19] Neurogenesis occurs throughout life in the subventricular zone (SVZ) and the subgranular zone of the dentate gyrus, [20][21][22] making them particularly susceptible to IR-induced apoptosis. 14,15,23,24 Therapeutic doses of irradiation (IR) result in increased apoptosis, 23,25 decreased cell proliferation and reduced stem/progenitor cell differentiation into neurons within the neurogenic regions, both in rodents 24,26 and in humans.…”
Section: Subject Category: Neurosciencementioning
confidence: 99%